Study of Innovative Behavior in Terms of Leadership Roles, Organizational Culture and Knowledge Sharing - Cahyaningtyas, Valentina Erna; Nuvriasari, Audita (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this research is to examine creative behavior through the lenses of leadership responsibilities, company culture, and information exchange. In this research, 117 participants were surveyed. The study tool used is a questionnaire, and the data gathering approach is a survey method. Data analysis in SmartPLS 3.2 makes use of the outer model, inner model, and hypothesis testing. Leadership does not have a major impact on innovative behavior, according to the study's conclusions. However, organizational culture does, and knowledge sharing also has a good and significant influence.